Differential association of cortical, subcortical and spinal cord damage with multiple sclerosis disability milestones: A multiparametric MRI study. (March 2022) - Hidalgo de la Cruz, Milagros; Valsasina, Paola; Meani, Alessandro; Gallo, Antonio; Gobbi, Claudio; Bisecco, Alvino; Tedeschi, Gioacchino; Zecca, Chiara; Rocca, Maria A; Filippi, Massimo
Background: In multiple sclerosis (MS), cortical, subcortical and infratentorial structural damage may have a differential contribution to clinical disability according to disease phases. Purpose: To determine the relative contributions of cortical, deep (D) grey matter (GM), cerebellar and cervical cord damage to MS disability milestones. Methods: Multi-centre 3T brain and cervical cord T2 - and three-dimensional (3D) T1 -weighted images were acquired from 198 MS patients (139 relapsing-remitting (RR) MS, 59 progressive (P) MS) and 67 healthy controls. Brain/cord lesion burden, cortical thickness (CTh), DGM and cerebellar volumetry and cord cross-sectional area (CSA) were quantified. Random forest analyses identified predictors of expanded disability status scale (EDSS) disability milestones (EDSS = 3.0, 4.0 and 6.0). Results: MS patients had widespread atrophy in all investigated compartments versus controls ( p -range: ⩽0.001–0.05). Informative determinants of EDSS = 3.0 were cord CSA, brain lesion volume, frontal CTh and thalamic and cerebellar atrophy (out-of-bag (OOB) accuracy = 0.84, p -range: ⩽0.001–0.05). EDSS = 4.0 was mainly predicted by cerebellar and cord atrophy, frontal and sensorimotor CTh and cord lesion number (OOB accuracy = 0.84, p -range: ⩽0.001–0.04). Cervical cord CSA ( p = 0.001) and cord lesion number ( p = 0.003) predicted EDSS = 6.0 (OOB accuracy = 0.77). Conclusion: Brain lesion burden, cortical and thalamic atrophy were the main determinants of EDSS = 3.0 and 4.0, while cord damage played a major contribution to EDSS = 6.0.